2022
DOI: 10.1093/iob/obac030
|View full text |Cite
|
Sign up to set email alerts
|

Size at Birth, Postnatal Growth, and Reproductive Timing in an Australian Microbat

Abstract: Reproductive phenology, size at birth and postnatal growth are important life history traits that reflect parental investment. The ability to document detailed changes in these traits can be a valuable tool in the identification and management of at-risk wildlife populations. We examined reproductive traits in a common, widespread Australian microbat, Chalinolobus gouldii, at two sites over two years and derived growth curves and age estimation equations which will be useful in the study of how intrinsic and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…Previous studies have demonstrated that phenology (repeated seasonal biological events) is a critical part of ecological relationships, and a primary indicator of species responses to climate change 15 . In a seasonal temperate zone, delayed fertilization, reduction in fetus development and timing of parturition could be affected by unfavorable climatic conditions in insectivorous bats 86 88 . Further surveys have revealed that under cool and wet conditions, delayed parturition and lactation by up to 1–2 weeks were evident in several vespertilionid bats 86 , along a delay of nearly 30 days in parturition dates and as well as a delay in birth synchrony in Antrozous pallidus 45 , Myotis lucifugus , Myotis yumanensis and Myotis cilioabrum 37 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that phenology (repeated seasonal biological events) is a critical part of ecological relationships, and a primary indicator of species responses to climate change 15 . In a seasonal temperate zone, delayed fertilization, reduction in fetus development and timing of parturition could be affected by unfavorable climatic conditions in insectivorous bats 86 88 . Further surveys have revealed that under cool and wet conditions, delayed parturition and lactation by up to 1–2 weeks were evident in several vespertilionid bats 86 , along a delay of nearly 30 days in parturition dates and as well as a delay in birth synchrony in Antrozous pallidus 45 , Myotis lucifugus , Myotis yumanensis and Myotis cilioabrum 37 .…”
Section: Discussionmentioning
confidence: 99%
“…These bats belong to the families Hipposideridae — Hipposideros terasensis (Cheng and Lee, 2002) and Hipposideros cineraceus (Jin et al , 2010); Phyllostomidae — Phyllostomus hastatus (Stern and Kunz, 1998) and Artibeus watsoni (Chaverri and Kunz, 2006); Pteropodidae — Rousettus leschenaulti (Elangovan et al , 2002), Cynopterus sphinx (Elangovan et al , 2003), Pteropus poliocephalus (Divljan et al , 2006; Welbergen, 2010), Pteropus sp. (Giannini et al , 2006), and Eidolon helvum (Hayman et al , 2012 b ); Molossidae — Tadarida brasiliensis (Allen et al , 2010); Thyropteridae — Thyroptera tricolor (Chaverri and Vonhof, 2011); Vespertilionidae — Myotis lucifugus (Baptista et al , 2000), Eptesicus fuscus (Hood et al , 2002), Pipistrellus pipistrellus (Hielscher et al , 2015), Scotophilus kuhlii (Chen et al , 2016), Myotis emarginatus (Eghbali and Sharifi, 2018), and Chalinolobus gouldii (Eastick et al, 2022). All these studies assessed morphological and quantifiable characteristics which can be tracked ordinally throughout the lifespan of a bat using methods that examined dental degradation, body mass growth, sexual maturity, fusion of the epiphysis, cranial bone fusion, tooth development and skeletal growth (Baptista et al , 2000; Cheng and Lee, 2002; Divljan et al , 2006; Giannini et al , 2006; Brunet-Rossinni and Wilkinson, 2009; Hielscher et al , 2015).…”
Section: Introductionmentioning
confidence: 99%
“…All these studies assessed morphological and quantifiable characteristics which can be tracked ordinally throughout the lifespan of a bat using methods that examined dental degradation, body mass growth, sexual maturity, fusion of the epiphysis, cranial bone fusion, tooth development and skeletal growth (Baptista et al , 2000; Cheng and Lee, 2002; Divljan et al , 2006; Giannini et al , 2006; Brunet-Rossinni and Wilkinson, 2009; Hielscher et al , 2015). Except for Divljan et al (2006) and Hayman et al (2012 b ), these studies used rapid, non-destructive methods that do not harm live animals or damage preserved specimens which enabled examination of either infant bats of known age (Stern and Kunz, 1998; Baptista et al , 2000; Cheng and Lee, 2002; Elangovan et al , 2002, 2003; Chaverri and Kunz, 2006; Allen et al , 2010; Chaverri and Vonhof, 2011; Eghbali and Sharifi, 2018; Eastick et al , 2022) or preserved specimens of unknown age (Giannini et al , 2006; Hielscher et al , 2015).…”
Section: Introductionmentioning
confidence: 99%